Transformation Du Paysage Oasien Du Souf Entre Tradition Et Modernité - Adaiak, Radja (University of Eloued جامعة الوادي, 2024)
Abstract: This study explores the historical and socio-economic development of the Souf region, situated on the periphery of the Grand Erg Oriental. It sheds light on urban landscapes and agricultural practices in response to the region's climatic and economic changes. Souf, formerly profoundly entrenched in conventional ways of living, confronts significant transformations propelled by contemporary advancements in agriculture and urbanization. Thus, the research underscores the intricate interaction between tradition and modernization. The findings highlight the substantial influence of these changes on the conservation of cultural heritage, prompting us to consider the implications. It also emphasizes the urgent need for the adaptation of agricultural practices to meet today's concerns, ensuring the sustainability of the region's unique cultural and agricultural heritage. Résumé: Cet article examine l'évolution historique et socio-économique de la région du Souf, dans les premiers replis du Grand Erg Oriental. L'étude met l’accent sur les changements climatiques et économiques, les transformations du paysage urbain et des pratiques agricoles, révélant l'interaction complexe entre tradition et modernisation. Le Souf, autrefois enraciné dans un mode de vie traditionnel, subit aujourd'hui des mutations radicales sous l'influence des développements agricoles et urbains contemporains. Les résultats soulignent l'impact de ces mutations sur la préservation du patrimoine culturel et l'adaptation des pratiques agricoles aux nouvelles réalités contemporaines
Keywords: Souf; région saharienne; paysage urbain; pratiques agricoles; modernisation; Saharan region; urban environment; farming methods; modernization